Knowledge networks and their role in shaping the relations within the Agricultural Knowledge and Innovation System in the agroenergy sector. The case of biogas in Tuscany (Italy). (November 2017) - Gava, Oriana; Favilli, Elena; Bartolini, Fabio; Brunori, Gianluca
Abstract: This paper presents an analysis of the knowledge retrieval networks behind the adoption of farm biogas in an area of Mediterranean Europe featuring arable farming systems. The overarching objective of the analysis is to help and understand the interplay between biogas adopters and the stakeholders of the Agricultural Knowledge and Innovations System (AKIS). Specifically, the paper proposes an application of social network analysis that aims at bringing out the influence of knowledge exchanged within the system on adopters' business decisions, as well as adopters' contribution to knowledge upgrading. Social network analysis focuses on the estimation of three network attributes (cohesion, knowledge co-creation, and brokerage) using primary data, collected in 2015 via questionnaire to plant adopters. Self-education, upstream industry, agronomists, farmer/biogas unions, university, public-funded projects, and public research centers are AKIS' stakeholders, which adopters turn to when seeking for information and/or know-how. Upstream industry is the most influential node and the one that can help knowledge diffusion across adopters, regardless of their background. Self-accessible resources are major providers of information at the adoption-decision stage. The networks are centralized on self-education tools, while upstream industry and the Research Center on Animal Productions are the brokers. Policy intervention aimed at improving AKIS in the biogas sector should involve the upstream industry in decision-making, while considering the duality of self-accessible information vs. physical advisors. This paper shows evidence from a region where public incentives have allowed biogas diffusion, despite the region not being intrinsically suitable for it. Study findings may be useful for policy-makers and researchers who deal with the prevention, or mitigation, of the negative externalities of land use change via the promotion of informed technology diffusion. Highlights: Improving knowledge networks may help the adoption of innovation in the bioeconomy. A social network analysis of the Agricultural Knowledge and Innovation System of biogas is proposed. Besides self-information, upstream industry and the Research Centre on Animal Productions play key roles within the System. Policy to improve AKIS should involve the upstream industry.